Citric Acid Catalyzed Aqua Mediated Multicomponent Synthesis of Tetrahydropyridines and its Antioxidant Activities - Divya Dogra; Ruchi Bharti; Renu Sharma (Orbital: The Electronic Journal of Chemistry, 2020)
Tetrahydropyridine derivatives are one of the most demanding molecules due to its great applications in medicinal and synthetic chemistry. Here we have designed a new way to synthesize a series of tetrahydropyridine derivatives using citric acid. In this methodology, five-component reaction of 1,3-diketones, substituted amines and aldehydes is done in the presence of citric acid extracted from lemon juice. High atom economy, green and mild conditions, high to moderate yields and shorter reaction times were the key features of this methodology. Later, we have discussed the antioxidant activities of our compounds. It is observed that compound 4a, 4b, 4e, 4f, 4i and 4l were quite effective to show good antioxidant activity.DOI: http://dx.doi.org/10.17807/orbital.v12i4.1550